2017
DOI: 10.1017/jmech.2017.48
|View full text |Cite
|
Sign up to set email alerts
|

Linear Stability Analysis of Journal Bearings Lubricated With a Non-Newtonian Rabinowitsch Fluid

Abstract: The linear stability boundaries of journal bearings lubricated with a non-Newtonian fluid have been investigated in this paper. Based on the Rabinowitsch fluid model, a non-Newtonian dynamic Reynolds equation for journal bearings is derived and then applied to analyze the linear dynamic characteristics of short journal bearings. Comparing with the Newtonian-lubricant case, the non-Newtonian rheology of dilatant lubricants provides a larger area of linearly stable region. However, the non-Newtonian properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Khonsari and Chang 1 studied the stability boundary of short bearings based on journal centre trajectories, and found the expression of threshold speed expressed by stiffness and dampness coefficients by applying the Routh Hurwitz stability criterion on the stability characteristic equation of the journal bearing. Lin et al 2,3 discussed the effects of non-Newtonian lubricants (couple stress fluids 2 and Rabinowitsch fluids 3 ) on the linear stability of journal bearings. Tian and Chen 4 expanded the range of non-Newtonian factor during the discussion of the linear stability of journal bearings lubricated with Rabinowitsch fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Khonsari and Chang 1 studied the stability boundary of short bearings based on journal centre trajectories, and found the expression of threshold speed expressed by stiffness and dampness coefficients by applying the Routh Hurwitz stability criterion on the stability characteristic equation of the journal bearing. Lin et al 2,3 discussed the effects of non-Newtonian lubricants (couple stress fluids 2 and Rabinowitsch fluids 3 ) on the linear stability of journal bearings. Tian and Chen 4 expanded the range of non-Newtonian factor during the discussion of the linear stability of journal bearings lubricated with Rabinowitsch fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Considering non-Newtonianism of the lubricant, Lin et al 2 illustrated the influence of couple stress on the nonlinear stability of short hydrodynamic bearings. Several years later, applying Rabinowitsch fluid model, Lin et al 3 discussed the linear stability of short hydrodynamic bearings lubricated with pseudoplastic fluids. To solve the Reynolds equation, perturbation method was applied by them which means that the non-Newtonian factor of the pseudoplastic lubricant cannot be larger than 1.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al 29 theoretically investigated the linear dynamic performance of short journal bearing simulated with non-Newtonian Rabinowitsch flow model. They have calculated the simulation results for Newtonian, dilatants, and pseudo-plastic fluids and have observed that dilatants/ pseudo-plastic fluids show a reverse trend in the stable region for short bearing.…”
Section: Introductionmentioning
confidence: 99%